Hintsa-hyvinvointiohjelman vaikutukset aikomuksiin ja fyysiseen aktiivisuuteen rahoitusalan yrityksessä - Hintsa, Eleonoora (2018)
There is more information available concerning the impact of physical activity and inactivity on health than ever before. Yet, numerous people exercise inadequately to benefit their health. The problem is recognized as behavioral and therefore a variety of theories to explain and predict physical activity have been developed. Ajzen’s (1991) Theory of Planned Behavior (TPB) has been discovered to explain and predict physical activity particularly well (Linder, Harper, Jung & Woodson-Smith 2017). According to the theory all behavior is preceded by intention based on attitude, subjective norm and perceived behavioral control. These cognitive constructs are based on a set of underlying beliefs, which according to their accessibility impact intention. The objective of this study was to assess the impact of a Hintsa-health training program on health enhancing physical activity (HEPA) using the TPB as the theoretical framework. Changes in HEPA- and TPB-variables, as well as the role of the specific behavior change techniques (BCT) and sources of delivery on said changes, were investigated within a group of finance employees taking part in the Hintsa- program. Data concerning the entire population was gathered through IPAQ and TPB questionnaires and understanding of individual-level processes was deepened through theme interviews. Statistical significance levels of the changes were tested as well as variable correlation significance. The theme interviews were analyzed and interpreted using categorizing content analysis. The changes in the quantitative data (n=14) were small and statistically insignificant and no significant correlation was found between variables of interest. However, the interviews showed clear changes in HEPA and TPB variables, most notably in intentions and attitudes. Participants increased their everyday-activity and mobility exercise, but not strength or aerobic training, even though positive attitudes and intention grew towards them all. There was considerable variance in experiences regarding BCTs and sources of delivery, which impacted adherence to the program. Small population sample (12% of the employees) and limitations in the word-framing in the questionnaire explain contradictions in quantitative and qualitative results. The impact of positive attitudes towards light exercise on intention and overall physical activity is suggested as a topic for future research.